2015
DOI: 10.3319/tao.2014.12.02.03(eosi)
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term (1982 - 2012) Summertime Sea Surface Temperature Variability in the Taiwan Strait

Abstract: Long-term (1982-2012) advanced very-high-resolution radiometer (AVHRR) data collected at a resolution of 0.04° clearly indicated sea surface temperature (SST) warming and variations associated with El Niño and Southern Oscillation (ENSO) in the Taiwan Strait (TS) during the summer. From 1982-2012 the spatially averaged warming trend in the TS was 0.057°C y-1. However, during the last 10 years the warming phenomenon appears to have halted and a slight cooling rate (0.03°C y-1) was observed. The monthly SST tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In the future, we hope to evaluate the performance of our models through various habitat classification methods. The global trend of sea temperature rise exerts substantial impacts on fisheries and ecosystems [77,90]. Shifts in environmental characteristics under the impacts of climate change mean that some habitats are no longer suitable for certain species; such impacts affect the entire ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we hope to evaluate the performance of our models through various habitat classification methods. The global trend of sea temperature rise exerts substantial impacts on fisheries and ecosystems [77,90]. Shifts in environmental characteristics under the impacts of climate change mean that some habitats are no longer suitable for certain species; such impacts affect the entire ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the discussion above, it has been observed that the SST near the Luzon Strait and the northern SCS (NSCS, in the region of 105-120 • E, 10-25 • N) in the highdamage periods was higher than that in the low-damage period. Some researchers report that the interdecadal changes in SST are related to the PDO [63,64]. As an extension, we further investigated the relationship between the PDO and NSCS's SSTs, revealing a weak correlation of only 0.2.…”
Section: The Relationship Between the Nscs Sst And Luzon Strait Trans...mentioning
confidence: 84%
“…In general, key features of composite positive MEI events (warm, El Niño) include: (1) atmosphere interaction and heat exchange. Changes of wind will affect the variability in the sea surface temperature, upper ocean temperature, mixed layer depth, and direction and strength of near surface wind-driven currents directly [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The El Niño events have been suggested to cause strong southwesterly winds over the western North Pacific in the summer [60]. According to the empirical orthogonal function analysis on the long-term summertime SST data of the TS during 1982-2012 [59], a warming trend in the TS was observed with the spatially average warming of 0.057 • C y −1 and an interannual variation in the SST was found after 1994, which was strongly correlated with the wind speed of the southwesterly monsoon. Strengthening winds enhanced the upwelling along the China coast, eastern Taiwan Banks, and the region south of Peng-Hu Islands, whereas the SST in eastern TS increased because of the increased transport of warm SCSSC.…”
Section: Discussionmentioning
confidence: 99%